GAMBARAN KADAR HEMOGLOBIN PADA MAHASISWI PROGRAM STUDI D3 ANALIS KESEHATAN UNIVERSITAS ABDURRAB DENGAN SIKLUS MENSTRUASI TIDAK TERATUR - Fatma Fatma; Rosa Devitria; Amanda Dwinta Harianti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Irregular menstrual cycles may alter the amount of blood loss during menstruation and potentially affect hemoglobin (Hb) levels. Persistent decreases in hemoglobin levels can increase the risk of anemia among adolescent girls and female college students. This study aimed to describe hemoglobin levels among female students of the D3 Health Analyst Study Program at Abdurrab University who experienced irregular menstrual cycles. This research employed a quantitative descriptive design with a cross-sectional approach. A total of 30 respondents were selected using purposive sampling according to the inclusion criteria. Hemoglobin levels were measured using the Cyanmethemoglobin method with a spectrophotometer. The results showed that 19 respondents (63.3%) were classified as anemic with Hb levels 12 g/dL, while 11 respondents (36.7%) had normal Hb levels. Based on menstrual cycle characteristics, 17 respondents (56.7%) had cycles longer than 35 days, and 13 respondents (43.3%) had cycles shorter than 21 days. Among respondents with menstrual cycles shorter than 21 days, 11 were anemic and only 2 had normal Hb levels. It can be concluded that most female students with irregular menstrual cycles experienced anemia, particularly those with menstrual cycles shorter than 21 days.Keywords: Hemoglobin, Namenia, Irregular Menstrual Cycle, Female Students.